Report of the Association of Coloproctology of Great Britain and Ireland/British Society of Gastroenterology Colorectal Polyp Working Group: the development of a complex colorectal polyp minimum dataset. (January 2017) - Chattree, A.; Barbour, J. A.; Thomas‐Gibson, S.; Bhandari, P.; Saunders, B. P.; Veitch, A. M.; Anderson, J.; Rembacken, B. J.; Loughrey, M. B.; Pullan, R.; Garrett, W. V.; Lewis, G.; et al.
Abstract: Aim: The management of large non‐pedunculated colorectal polyps (LNPCPs) is complex, with widespread variation in management and outcome, even amongst experienced clinicians. Variations in the assessment and decision‐making processes are likely to be a major factor in this variability. The creation of a standardized minimum dataset to aid decision‐making may therefore result in improved clinical management. Method: An official working group of 13 multidisciplinary specialists was appointed by the Association of Coloproctology of Great Britain and Ireland (ACPGBI) and the British Society of Gastroenterology (BSG) to develop a minimum dataset on LNPCPs. The literature review used to structure the ACPGBI/BSG guidelines for the management of LNPCPs was used by a steering subcommittee to identify various parameters pertaining to the decision‐making processes in the assessment and management of LNPCPs. A modified Delphi consensus process was then used for voting on proposed parameters over multiple voting rounds with at least 80% agreement defined as consensus. The minimum dataset was used in a pilot process to ensure rigidity and usability. Results: A 23‐parameter minimum dataset with parameters relating to patient and lesion factors, including six parameters relating to image retrieval, was formulated over four rounds of voting with two pilot processes to test rigidity and usability. Conclusion: This paper describes the development of the first reported evidence‐based and expert consensus minimum dataset for the management of LNPCPs. It is anticipated that this dataset will allow comprehensive and standardized lesion assessment to improve decision‐making in the assessment and management of LNPCPs.